Oswald von Nell-Breuning weiterdenken - Emunds, Bernhard; Rixen, Stephan (2022)
The current crises can only be overcome through solidarity. The concept of solidarity was central to the thinking of Oswald von Nell-Breuning SJ (1890–1991), the most important German academic of Catholic social teaching in the 20th century. In this book, renowned experts from the fields of theology, social science, political science, law, and history investigate impulses from the reception of his work. Their topics are the challenges posed by socio-ecological transformation, affordable housing, social services and trade union representation of interests under the conditions of digitalisation, as well as the church labour law. With contributions by Julian Degan, Prof. Dr. Bernhard Emunds, Prof. Dr. Stefan Greiner, Prof. Dr. Hermann-Josef Große Kracht, Prof. em. Dr. Hans Günter Hockerts, Prof. Dr. Tanja Klenk, Hannah Klinkenborg, Prof. Dr. Gerhard Kruip, Dr. Arnd Küppers, Erzbischof Reinhard Kardinal Marx, Prof. Dr. Stephan Rixen and Prof. Dr. Thomas Schüller.